Comparative Analysis of Reward Systems in Manufacturing Companies - Nazwa Nurrahmawati; Sabila Uluhiyah; Anggi Rizky Imania; Erika Mustika Putri; Indah Austin; Ninuk Riesmiyantiningtyas (Universitas Muhammadiyah Purwokerto, 2026)
This article examines a comparative analysis of reward systems in manufacturing companies. Reward systems are a critical aspect of human resource management because manufacturing work environments require high productivity, punctuality, and consistent work quality. This topic is significant since differences in the implementation of reward systems across companies may influence employee satisfaction, loyalty, and work effectiveness, which directly affects organizational competitiveness. This study employs a descriptive quantitative approach using a literature review method. Data were obtained from national and international scientific journals relevant to reward systems in the manufacturing industry. Data collection was conducted by reviewing, comparing, and analyzing previous studies related to financial, non-financial, intrinsic, and extrinsic reward systems. The findings indicate that manufacturing companies generally implement a combination of financial and non-financial rewards such as salaries, bonuses, incentives, recognition, promotion opportunities, and training programs. Reward systems that are implemented fairly, transparently, and in a balanced manner are proven to enhance employee motivation, job satisfaction, and performance, thereby supporting productivity and organizational sustainability.